Hubungan Health Literacy dengan Tingkat Kecemasan Pada Peserta Vaksinasi Covid-19 di Wilayah Kerja Puskesmas Pajang Surakarta - Fitriani, Nurlaila; Hasnawati, Atik (Alauddin Scientific Journal of Nursing, 2023)
Introduction : SARS-CoV-2 is a new virus in the coronavirus family that causes corona virus disease 19 (Covid-19). One of the goverment’s efforts to break this chain is by vaccinating the entire community. However, many people still show an attitude of doubt an anxiety about vaccines due to the many hoax circulating about vaccines and public doubts about the effectiveness of vaccines. The absence of validity control by the author on the uplouded news and the lack of health literacy by the public have led to many negative perceptions and anxiety felt by the public about vaccination. Objective : This study was conducted to determine the relationship between health literacy and the level of anxiety among participants of Covid-19 vaccination in the working area of Puskesmas Pajang Surakarta. Methods : The research method used is quantitative research with a descriptive correlative research design model using a cross sectional approach. This study uses accidental sampling technique with a total sample of 83 respondents. The research questionnaires used were HLS-EU-Q16 and DASS-42. Results : The results showed that there was a relationship between health literacy and anxiety levels and the R value = -0,760. Conclusion : There is a significant relationship between health literacy and the level of anxiety among participants in the Covid-19 vaccination in the working area Puskesmas Pajang Surakarta.